Comparison of Metformin and Ethinyl Estradiol-Cyproterone Acetate in the Management of Polycystic Ovary Syndrome - Sadaf Ajaib, Maimoona Ali (Journal of Rawalpindi Medical College, 2018)
Background: To compare ethinyl estradiol-cyproterone acetate and metformin for polycystic ovarian syndrome in terms of mean hirsutism score and waist hip ratio (WHR). Methods: A total of 120 patients (60 patients in each group) were included in the study. Group-A received metformin 500mg and group-B was given ethinyl estradiol 35 mg as treatment of polycystic ovary disease (PCOD), mean hirsuitism and waist to hip ratio was measured at 6months. Hirsuitism was measured according to Ferriman Gallway score. Circumferences were measured with an anthropometric tape over light clothing. Waist girth was measured at the minimum circumference between the iliac crest and the rib cage and hip girth at the maximum width and their ratio was calculated as baseline and after 6 months of treatment. Results: Mean age was 25.87±6.46 and 25.60±6.74, respectively. Mean waist hip ratio at presentation and after 6 months was proportionate in the two groups. Mean hirsutism score at baseline was tantamount in both groups but at 6 months significant reduction (p<0.001) was seen in Group-B (Ethinyl estradiol Cyproterone acetate) when compared with Group-A (Metformin). Mean BMI was 29.77±3.77 and 29.82±3.02 in group-A and B, respectively. Stratification with regard to age and BMI in terms of waist to hip ratio and mean hirsutism score was also carried out. Conclusion: Ethinyl estradiol cyproterone acetate (EE-CA) proved beneficial for reduction of mean hirsutism score in patients with PCOS, but it has no role in reducing WHR when compared with metformin.